Overcoming Insecurity among Generation Z in the Perspective of Tafsir Al-Munir - Saffitri, Widya Yulita; Nasution, Muhammad Ali Azmi (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2024)
Generation Z is the cohort of individuals born between 1996 and 2010. The group is prone to feelings of inferiority and insecurity. Insecurity is defined as a state of feeling inferior and insecure about oneself. Those who experience feelings of insecurity typically experience feelings of fear, embarrassment, or a lack of confidence. Such feelings can have a detrimental impact on social wellbeing and have an impact on a person's psychology. The objective of this study is to identify the factors that contribute to the insecurity experienced by Gen Z and to propose solutions based on the insights of Sheikh Wahbah al-Zuhayli in Tafsir Al-Munir. This research employs a qualitative approach, involving a comprehensive review of relevant literature, including books, scientific journals, academic research, and Tafsir Al-Munir. This study concludes that there are several factors that can trigger a person to feel insecure, including physical, economic, and achievement factors. The findings of this study are anticipated to assist Generation Z in overcoming insecurity in accordance with the perspective of Tafsir Al-Munir, thereby motivating them to maintain a positive self-image and a grateful attitude.